2021
DOI: 10.3390/ph14050391
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cellular and Cancer Stem Cell-Related Putative Gene Expression of Parental and CD44+CD24− Sorted MDA-MB-231 Cells by Cisplatin

Abstract: Triple-negative breast cancer (TNBC) is an aggressive breast cancer subtype that promotes a higher risk of metastasis and cancer reoccurrence. Cisplatin is one of the potential anticancer drugs for treating TNBC. However, the occurrence of cisplatin resistance still remains one of the challenges in fully eradicating TNBC. The presence of cancer stem cells (CSCs) has been proposed as one of the factors contributing to the development of cisplatin resistance. In this study, we aimed to characterize the cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Further, we measured the IC 50 of all the compounds (Table 2) in another TNBC cell line (4T1 cell/mouse‐derived) and results showed that compound 9h showed similar efficacy (compared with MDA‐MB‐231) in 4T1 as well (12.55 ± 0.8 µM). It was reported that cisplatin treatment in MCF‐7 and MDA‐MB‐231 cells showed IC 50 of 16.3 ± 0.53 µM and 48.1 ± 0.34 µM respectively (Koh et al, 2021; Ray et al, 2007; Vasdev et al, 2018). Compared with IC 50 of cisplatin, compound 9h showed superior activity in all three cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we measured the IC 50 of all the compounds (Table 2) in another TNBC cell line (4T1 cell/mouse‐derived) and results showed that compound 9h showed similar efficacy (compared with MDA‐MB‐231) in 4T1 as well (12.55 ± 0.8 µM). It was reported that cisplatin treatment in MCF‐7 and MDA‐MB‐231 cells showed IC 50 of 16.3 ± 0.53 µM and 48.1 ± 0.34 µM respectively (Koh et al, 2021; Ray et al, 2007; Vasdev et al, 2018). Compared with IC 50 of cisplatin, compound 9h showed superior activity in all three cell types.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CSCs are intrinsically resistant to conventional therapies including chemo and radiotherapy, that mainly target high proliferative cells. CSCs are usually in a low-cycling quiescent state, which makes them almost unaffected by conventional cytotoxic agents ( 34 ).…”
Section: Cancer Stem Cells and Sulforaphanementioning
confidence: 99%
“…Table 2 shows the predicted IC 50 values of compounds 1-4, calculated by the statistical tool GraphPad Prism 8, and of the positive control cisplatin [16][17][18] for human adenocarcinoma breast cancer (MDA-MB-231) and nontumorigenic (MCF-10A) cell lines.…”
Section: Cytotoxicity Effects Of Compounds 1-4mentioning
confidence: 99%
“…[24] However, despite different studies describing the evaluation of the cytotoxic activity of semisynthetic derivatives of ent-kaurenoic acid, [25,26] no previous works report the selectivity against MDA-MB-231, an aggressive type of human breast adenocarcinoma cell line. .0 [16,17] MDA-MB-231 1566.0 1401.0 3072.0 1900.0 143.0 [17,18]…”
Section: Cytotoxicity Effects Of Compounds 1-4mentioning
confidence: 99%